Idiopathic intracranial hypertension. Case report and literature review - Lauruvėnaitė , L.; Raugalas , R.; Grikinienė , J. (Neurologijos seminarai, 2020)
We report a clinical case of 11 year old patient presenting with dizziness, diplopia, and blurred vision. The patient did not have headache. Ophthalmologic examination revealed papilledema in both eyes, lumbar puncture showed an increased intracranial pressure, magnetic resonance imaging and angiography identified no structural cerebral lesions, only optic disc bulging in both eyes. The patient had one risk factor – overweight; puberty had not yet begun. She was administered dehydrating medical therapy of acetazolamide and mannitol. With pharmacological treatment not being effective enough, ventriculoperitoneal shunting operation was performed, after which symptoms of intracranial hypertension disappeared. After one year of follow-up, the patient reported no symptoms of intracranial hypertension, she did not experience any complications with the shunt; however, thinning of retinal nerve fiber layer and optic nerve atrophy was found in both eyes and a severe decline of visual function in one eye. Idiopathic intracranial hypertension is rare among children and can have a less distinct clinical presentation. Therefore, it is necessary to have this in mind even when the patient is presenting with less specific intracranial hypertension symptoms. In the case of declining visual function, urgent surgical treatment is required to preserve vision. Ventriculoperitoneal shunting is effective in managing symptoms of intracranial hypertension, however, in some cases visual function keeps declining.